Pengembangan Media Pembelajaran Interaktif Berbasis Website dengan Berbantuan Lectora inspire Untuk Meningkatkan Hasil Belajar IPAS - Dika Inayati; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2024)
This research is motivated by the lack of technology utilization in the development of learning media at SDN Kaliwungu 02, which impacts student learning outcomes. The type of research used is Research and Development (R&D) with the ADDIE development model. This study aims to develop and test the feasibility, practicality, and effectiveness of interactive web-based learning media assisted by Lectora Inspire. The population in this study consisted of 36 children, with 12 subjects for small-scale trials and 24 children for large-scale trials. Validation results by material and media experts showed 88.5%, which falls into the feasible category. Based on pretest and posttest results, it was found that this interactive learning media is effective in improving student learning outcomes, as evidenced by the increase in the average pretest score from 62 to 83 at posttest and an N-gain test result showing a gain value of 0.77 in the high category. Based on the questionnaire responses collected, very positive feedback was obtained from both teachers and students. From these results, it can be concluded that interactive web-based learning media assisted by Lectora Inspire is effective in improving IPAS learning outcomes and is feasible and practical for use in the learning process for grade IV students at SDN Kaliwungu 02.